2020
DOI: 10.1113/ep087834
|View full text |Cite
|
Sign up to set email alerts
|

Do females and males exhibit a similar sarcopenic response as a consequence of normoxic and hypoxic bed rest?

Abstract: This study investigated the effects of hypoxia on the known processes of adaptation of body composition and muscle function to normoxic inactivity. Females (n = 12) and males (n = 11) took part in the following interventions: hypoxic ambulation (HAMB; ∼4000 m); hypoxic bed rest (HBR; ∼4000 m) and normoxic bed rest (NBR). Prior to and immediately following each intervention, body composition, thigh and lower leg crosssectional area (CSA) and isometric muscular strength were recorded. Participants lost body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Indeed, force and endurance measurements performed in healthy participants (Clark et al., 2003 ; Fulco et al., 1999 ; Maughan et al., 1986 ; Russ & Kent‐Braun, 2003 ), and following limb immobilization (Semmler et al., 1999 ), repeatedly highlight that women have greater endurance capacity for isometric and dynamic muscle contractions compared to men. While functional decrements, as compared to simple force production, following unloading are sometimes observed to a greater extent in women (Deschenes et al., 2009 ; Wu et al., 2022 ; Yasuda et al., 2005 ), it is not always the case (de Carvalho et al., 2022 ; Mekjavic et al., 2021 ; Miles et al., 2005 ). In our animals, we observed greater improvement in muscle function after 7 days of recovery at full weight‐bearing in females than in males, and studies performed in humans have found similar results in participants recovering from immobilization (Semmler et al., 1999 ) and muscle exhaustion (Fulco et al., 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, force and endurance measurements performed in healthy participants (Clark et al., 2003 ; Fulco et al., 1999 ; Maughan et al., 1986 ; Russ & Kent‐Braun, 2003 ), and following limb immobilization (Semmler et al., 1999 ), repeatedly highlight that women have greater endurance capacity for isometric and dynamic muscle contractions compared to men. While functional decrements, as compared to simple force production, following unloading are sometimes observed to a greater extent in women (Deschenes et al., 2009 ; Wu et al., 2022 ; Yasuda et al., 2005 ), it is not always the case (de Carvalho et al., 2022 ; Mekjavic et al., 2021 ; Miles et al., 2005 ). In our animals, we observed greater improvement in muscle function after 7 days of recovery at full weight‐bearing in females than in males, and studies performed in humans have found similar results in participants recovering from immobilization (Semmler et al., 1999 ) and muscle exhaustion (Fulco et al., 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, information regarding nutritional status (i.e., change score and CV of actual vs. targeted energy intake; Supplementary Table 2) was collected for the three studies. Results for some of these outcomes from each individual study have been published elsewhere (Debevec et al, 2014;McDonnell et al, 2019McDonnell et al, , 2020Mekjavic et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the level of oxygen, men and women show sex-dependent differences in their muscle tissue composition (31). Compared with normoxic bed rest, hypoxic bed rest led to larger reductions of thigh cross-sectional area in females than in males (32). Besides sex-dependent muscle tissue differences, metabolic differences at altitude between women and men should be considered.…”
Section: Discussionmentioning
confidence: 99%